STRAW AND DIFFERENT SEEDER SPEEDS - Ribeiro, Bruna da S. B.; Silva, Leonardo B.; Souza, Jarlyson B. C. [UNESP]; Sousa, Washington da S.; Almeida, Edmilson I. B.; da Silva, Rouverson P. [UNESP] (FapUNIFESP (SciELO), 2024)
In the satisfactory development of soybeans an ally is quality seeding and soil preparation. The aim was to evaluate the quality of soybean seeding under different speeds and cover crops. The experiment was conducted in a commercial soybean crop, using a highperformance pneumatic seeder. The design experimental was randomized blocks, in 2x2 strip arrangement and nine repetitions. The factors consisted of two seeding speeds (7.0 km h-1 and 8.5 km h-1) and two cover crops (Urochloa brizantha cv. Marandu and Urochloa ruziziensis). The operational quality was analyzed by statistical quality control, statistical process control and boxplot. It was found that U. ruziziensis provided more uniformity of coverage and soil humidity than U. brizantha cv. Marandu, but with lower straw produced. It is recommended speeds of 7.0 and 8.5 km h-1 for no-till soybean in U. ruziziensis straw, and 7.0 km h-1 in U. brizantha cv. Marandu straw.
Keywords: boxplot; control charts; cover crop; Glycine max (L.) Merrill; seeding speed